PERUBAHAN TINGKAT KERAPATAN VEGETASI MENGGUNAKAN LANDSAT 8 DI DESA SEDOA KECAMATAN LORE UTARA KABUPATEN POSO - Rizki, Muhammad Arya; Akhbar, Akhbar; Misrah, Misrah (Universitas Tadulako, 2020)
The location of the boundary of Sedoa Village is in the north of Parigi Moutong Regency, in the south there is Sigi Regency, in the east of Poso Pesisir District and in the west of Watumaeta Village. Changes in land use change or encroachment. Therefore, research is needed to analyze changes in the level of vegetation density in Sedoa Village, North Lore Subdistrict, Poso Regency using Geographic Information Systems (GIS). This research was conducted for 3 months, from August to November 2019 in Sedoa Village, North Lore District, Poso Regency. The method used in this research is descriptive method with NDVI (Normalized Difference Vegetation Index) analysis to obtain data directly on a computer using Landsat 8 imagery and ArcGis 10.4 software, as well as field surveys to test accuracy with the method of taking coordinate points. Based on the results of the NDVI (Normalized Difference Vegetation Index) change using Landsat 8 imagery recording 20 October 2013 and 3 September 2019 Path 114 Row 61 in Sedoa Village, North Lore District, Poso Regency. Changes in the level of density in the research location on dryland agricultural land cover with an area of 1,021.04 Ha (10.3%), for the shrub category had an area change of 273.06 Ha (2.7%), the secondary dryland forest category changed by 2,077, 37 Ha (20.9%) and changes in the primary dryland forest area of 6,581.82 Ha (66.1%) with a total change of 9,953.29 Ha.Keyword : Descriptive Method With NDVI.